Development and preliminary validation of the sport injury-related growth inventory. - Santi, Giampaolo; Carraro, Attilio; Mellalieu, Stephen D.; Wadey, Ross (International Journal of Sport & Exercise Psychology, 2024)
Aligned with research recommendations (e.g., Wadey & Everard, 2021), the purpose of this multi-method multi-study investigation was to construct a measure of athletes' experiences of growth following sport injury. Study 1 systematically reviewed the literature on sport injury-related growth (SIRG) and extracted a pool of relevant and specific items organised in themes. In Study 2, a panel of experts (i.e., academics, sport psychologists, and previously injured athletes) was asked to quantitatively and qualitatively assess the items for relevance, clarity, and specificity. These two studies provided evidence for the content validity of the pool of items. Study 3 tested the psychometric properties of the instrument on a sample of previously injured athletes (N = 452), identifying satisfactory factor structure, concurrent validity, and reliability. Collectively, the multi-study supports the construct validity of a 24-item scale, named the Sport Injury-Related Growth Inventory-24 (SIRGI-24), measuring eight sub-dimensions of SIRG: sense of mastery, positive relations with others, responsibility for one's health, self-awareness, emotional ability, purpose in life, purpose in sport, and body awareness. To conclude, the SIRGI-24 allows researchers and sport psychologists to assess the SIRG experienced by injured athletes.